1981
DOI: 10.1021/bi00512a046
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of ribonucleic acid. A direct study by carbon-13 nuclear magnetic resonance spectroscopy

Abstract: Direct study of the methylation of ribonucleic acid with methyl methanesulfonate by carbon-13 nuclear magnetic resonance spectroscopy has demonstrated the usefulness of this method in studying the chemical modification of biomacro-molecules and the interaction between nucleic acids and biologically active agents. This direct stable isotope method eliminated all tedious and questionable degradation processes for determining the reactive sites and the product distributions. Six methylated products, 7-methylguano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Here, we have shown that [ 14 C]MeI treatment of tRNA introduces 1-meG lesions, and that these lesions are repaired by AlkB. Previous studies have shown that 1-meG is the major methylation product obtained by MeI treatment of guanosine under basic conditions (28), and that other methylating agents can induce 1-meG in RNA and DNA in vitro (16)(17)(18) and in vivo (22). We also attempted to introduce 1-meG residues in DNA by treatment of a G-rich oligonucleotide with [ 14 C] MeI, but were unsuccessful (P. Ø. Falnes and R. F. Johansen, unpublished data).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Here, we have shown that [ 14 C]MeI treatment of tRNA introduces 1-meG lesions, and that these lesions are repaired by AlkB. Previous studies have shown that 1-meG is the major methylation product obtained by MeI treatment of guanosine under basic conditions (28), and that other methylating agents can induce 1-meG in RNA and DNA in vitro (16)(17)(18) and in vivo (22). We also attempted to introduce 1-meG residues in DNA by treatment of a G-rich oligonucleotide with [ 14 C] MeI, but were unsuccessful (P. Ø. Falnes and R. F. Johansen, unpublished data).…”
Section: Discussionmentioning
confidence: 77%
“…1-meA and 3-meC are methylated at N-atoms that are involved in Watson-Crick base pairing of the corresponding normal bases, and this is also the case for 1-meG and 3-meT. Although less prevalent than 1-meA and 3-meC, both 3-meT and 1-meG have been reported to be introduced upon treatment of DNA or RNA with alkylating agents, both in vitro (16)(17)(18)(19)(20) and in vivo (21,22). In the present study, we report that both 1-meG and 3-meT can be repaired by AlkB proteins from humans and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…These adducts can be readily detected by reverse-transcription analysis, as the modification at the Watson-Crick face induces premature cDNA termination or, in the MaP strategy, incorporation of a noncomplementary nucleotide. While generally ignored, DMS also is known to methylate both G and U residues (Lawley and Shah 1972;Kusḿierek and Singer 1976;Chang and Lee 1981;Ashworth et al 1985). For example, DMS readily reacts with the N7 of the imidazole ring of G; however, N7 adducts do not efficiently interfere with conventional reverse transcription and are thus not typically detected in probing experiments (Ehresmann et al 1987).…”
Section: Resultsmentioning
confidence: 99%
“…For example, DMS readily reacts with the N7 of the imidazole ring of G; however, N7 adducts do not efficiently interfere with conventional reverse transcription and are thus not typically detected in probing experiments (Ehresmann et al 1987). G nucleotides can also be methylated at the N1 and N3 positions, and U nucleotides can be methylated at the N3 position, likely through mechanisms that involve transient base deprotonation or tautomerization (Lawley and Shah 1972;Kusḿierek and Singer 1976;Chang and Lee 1981;Ashworth et al 1985). These modifications are at the Watson-Crick face and thus should be detectable by reverse-transcription analysis.…”
Section: Resultsmentioning
confidence: 99%
“…2). Resonance signals attributable to the phosphate-bound methyl group of GMP-OMe [18,19] were easily spotted, as there were no similar counterparts in the absence of methanol. In addition, the effect induced by the methyl group in the resonances of certain GMP nuclei gave rise to upfield/downfield shifts such that some of the homologous nuclei in GMP and GMP-OMe could be distinguished from each other despite the proximity of their respective signals.…”
Section: Spectroscopic Analysismentioning
confidence: 99%